Peer-to-peer lending: Shift of pricing regime and changes in risk sensitivity - Chen, Jiakai; Huang, Wei; Wang, Xinruo (Journal of Banking & Finance, 2025)
We investigate the changes in risk sensitivities of interest rates following a shift in Prosper.com's pricing mechanism from auctions to posted prices. We find that the shift leads to reduced sensitivities of loan pricing to credit risk. Furthermore, this change results in higher profits for the platform while investors receive less compensation for the credit risk they undertake. Additionally, borrowers encounter less credit rationing. Analyses of repeat borrowers under both pricing regimes and tests with data under Prosper's upgraded posted prices confirm these findings. We argue that less risk-based pricing results from the incentives of the lending platform.